RISK COMMUNICATION REGARDING JADAR PROJECT - Between ethics, profession and politics - Kešetović, Želimir (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
Summary: The paper analyzes risk communication in the context of the Jadar project - a mining venture of the Rio Tinto company for the extraction of lithium in the Jadar valley. The communication of key actors: the Rio Tinto company, the ruling political structures in Serbia, the political opposition and non-governmental organizations and experts is monitored through the analysis of timelines of key events, press releases and discourses of various actors. In the conditions of insufficient knowledge of the objective dimensions of the hazard, a sharp polarization can be observed between the supporters/proponents of the project (the company itself, the ruling political structure and part of the experts) who believe that the potential dangers are within the acceptable range, and the possible profit is significant, and other communication actors who stand on the diametrically opposite point of view. The aggressive campaign of the government and the company in favor of the project resulted in an increase in the number of opponents of the project, which is understandable in the conditions of lack of trust in institutions, absence of a culture of dialogue, high corruption and a divided society. In order to get closer to the ideal risk communication as an exchange of true information between experts and laymen, the responsible authority that takes care of the general interest would have to completely change the pattern of behavior and place itself in the role of facilitator and mediator that enables an open dialogue of interested parties on the media with a national frequency.
Keywords: risk communication, Jadar project, Rio Tinto company, compradors, experts